Communicate to win - Denny, Richard (IG library, 2009)
Communicate to Win is full of sound, practical advice on every aspect of business and personal communication, such as how to: encourage people to like you, understand what motivates people, use the telephone effectively, excel at one-on-one conversation, develop your emotional intelligence, master a good writing style and give a great public presentation.